Integrating Core Culture into Orang Rimba Empowerment Strategies: A Stepping Stone Towards Achieving Sustainable Development Goals - Rina Astarika; Deki Zulkarnain (Indonesian Journal of Multidisciplinary Scientific Studies, 2024)
In pursuing the United Nations' Sustainable Development Goals (SDGs), adopting inclusive strategies that align with the unique cultures of marginalized communities is vital. This study emphasizes the critical role of weaving the Core Culture of the Orang Rimba community, a semi-nomadic group residing in Jambi, Indonesia, into existing empowerment strategies. Drawing from recent research trends, this study explores the promising potential of culture-based approaches, where integrating governmental policies with indigenous knowledge and practices can pave a more inclusive and sustainable developmental path. By delving deeper, we aim to foster a novel paradigm in sustainable development that resonates well with the intrinsic values and wisdom inherent in the Orang Rimba community. Central to this approach is an in-depth analysis of the Orang Rimba's Core Culture, presenting an opportunity to craft sustainable empowerment strategies deeply rooted in their rich cultural tapestry. Thus, this research pioneers a pathway that not only honors but actively incorporates the cultural heritage of the Orang Rimba community, catalyzing meaningful strides towards achieving the SDGs. Through this innovative approach, we aspire to unveil policies that are more receptive and inclusive, steering the community towards a brighter and more sustainable future.